"Endivide-se, o pagamento, você vê depois": uma análise da governança do fies e do impacto da dívida na vida do beneficiário. - Afonso José Duarte (2023)
The Student Financing Fund (FIES) has been an important research topic in studies of public administration, education, economics and many others. Since the program took on significant proportions during the Workers' Party governments, much criticism and praise has been made. Most of the works that embrace the FIES theme focus on evaluating the financial sustainability of the program, its contribution to the financialization process of the economy and the academic performance of students financed by the program. Professionals who graduated through the program and are dealing with the payment of debt ended up being forgotten by the research and evaluations carried out on the FIES. Our work, therefore, had the objective of evaluating the governance of the program from the perspective of the beneficiaries who were formed through it. Based on interviews with program beneficiaries and also on publications and comments taken from Facebook groups, we constructed an analysis of governance highlighting the communication and information circulating between government, banks, private higher education institutions (HEIs) and the beneficiaries themselves. Concomitantly, we entered the theme of private debt and the consequences of debt in the lives of indebted subjects. We chose discourse analysis as the methodological tool to help us interpret and understand the data collected in the field. From it, therefore, we perceive the existence of a very strong feeling of helplessness on the part of FIES beneficiaries. The government, banks and private HEIs end up making life difficult for beneficiaries due to the precariousness of the information disclosed and the difficulty in communicating with them. Debt, on the other hand, shapes the subjects' subjectivity and captures their possibilities for the future, demanding predictability from them